ECONOMIC EFFICIENCY OF IRRIGATION AND MINERAL NUTRITION IN WHITE HEAD CABBAGE SEED PRODUCTION IN CENTRAL CHERNOZEM REGION - A. F. Razin; A. F. Buharov; A. R. Buharova; O. A. Razin (Овощи России)
The combined use of fertilizers and irrigation allowed us to obtain maximum seed yield of white head cabbage up to 1,01 – 1,18 t/ha.  The best results were obtained when N120P180K120 was applied after one watering after planting. In this case, the relative net income was 1357 rubles/ha and the level of profitability reached 64.8%.